Clinically Distinct Phenotypes of Canavan Disease Correlate with Residual Aspartoacylase Enzyme Activity. Issue 5 (14th February 2017) - Mendes, Marisa I; Smith, Desirée EC; Pop, Ana; Lennertz, Pascal; Fernandez Ojeda, Matilde R; Kanhai, Warsha A; van Dooren, Silvy JM; Anikster, Yair; Barić, Ivo; Boelen, Caroline; Campistol, Jaime; de Boer, Lonneke; et al.
Abstract : A cohort of 14 Canavan patients with novel missense mutations could be divided into two phenotypically distinct groups (atypical/mild and typical/severe). We developed and implemented a method to study the effect of ASPA mutations at the enzyme level (aspartoacylase). This revealed a correlation between clinical presentation, enzyme activity and genotype in this cohort. The method is suitable to evaluate the effect of missense variants in patients with Canavan disease. ABSTRACT: We describe 14 patients with 12 novel missense mutations in ASPA, the gene causing Canavan disease (CD). We developed a method to study the effect of these 12 variants on the function of aspartoacylase—the hydrolysis of N‐acetyl‐l ‐aspartic acid (NAA) to aspartate and acetate. The wild‐type ASPA open reading frame (ORF) and the ORFs containing each of the variants were transfected into HEK293 cells. Enzyme activity was determined by incubating cell lysates with NAA and measuring the released aspartic acid by LC–MS/MS. Clinical data were obtained for 11 patients by means of questionnaires. Four patients presented with a non‐typical clinical picture or with the milder form of CD, whereas seven presented with severe CD. The mutations found in the mild patients corresponded to the variants with the highest residual enzyme activities, suggesting that this assay can help evaluate unknown variants found in patients with atypical presentation. We have detected a correlation between clinical presentation, enzyme activity, and genotype for CD.